Radiopharmacokinetic modelling and radiation dose assessment of 223Ra used for treatment of metastatic castration-resistant prostate cancer - Vera Höllriegl; Nina Petoussi-Henss; Kerstin Hürkamp; Juan Camilo Ocampo Ramos; Wei Bo Li (EJNMMI Physics)
Abstract Purpose Ra-223 dichloride (223Ra, Xofigo®) is used for treatment of patients suffering from castration-resistant metastatic prostate cancer. The objective of this work was to apply the most recent biokinetic model for radium and its progeny to show their radiopharmacokinetic behaviour. Organ absorbed doses after intravenous injection of 223Ra were estimated and compared to clinical data and data of an earlier modelling study. Methods The most recent systemic biokinetic model of 223Ra and its progeny, developed by the International Commission on Radiological Protection (ICRP), as well as the ICRP human alimentary tract model were applied for the radiopharmacokinetic modelling of Xofigo® biodistribution in patients after bolus administration. Independent kinetics were assumed for the progeny of 223Ra. The time activity curves for 223Ra were modelled and the time integrated activity coefficients, a ~ r S T D , $$ \overset{\sim }{a}\left({r}_S,T_D\right), $$ in the source regions for each progeny were determined. For estimating the organ absorbed doses, the Specific Absorbed Fractions (SAF) and dosimetric framework of ICRP were used together with the aforementioned a ~ r S T D $$ \overset{\sim }{a}\left({r}_S,T_D\right) $$ values. Results The distribution of 223Ra after injection showed a rapid plasma clearance and a low urinary excretion. Main elimination was via faeces. Bone retention was found to be about 30% at 4 h post-injection. Similar tendencies were observed in clinical trials of other authors. The highest absorbed dose coefficients were found for bone endosteum, liver and red marrow, followed by kidneys and colon. Conclusion The biokinetic modelling of 223Ra and its progeny may help to predict their distributions in patients after administration of Xofigo®. The organ dose coefficients of this work showed some variation to the values reported from clinical studies and an earlier compartmental modelling study. The dose to the bone endosteum was found to be lower by a factor of ca. 3 than previously estimated.